2012
DOI: 10.1007/s00038-012-0367-8
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood context and abuse among immigrant and non-immigrant women in Canada: findings from the Maternity Experiences Survey

Abstract: Objectives To examine the relationship between neighbourhood deprivation and concentration of immigrants, and abuse among immigrant women versus non-immigrant women. Methods Using data from the Canadian Maternity Experiences Survey (un-weighted sample N = 5,679 and weighted sample N = 68,719) linked to the neighbourhoods Census data, we performed contextual analysis to compare abuse prevalence among: immigrants B5 years, immigrants [5 years and Canadian-born. We identified two level effect modifiers: living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Other studies have reported lower rates of violence among pregnant immigrant women than we observed in this study [52,53], but found significant associations with poorer health behaviours, including not being current in vaccinations, not taking folic acid before pregnancy, and initiating prenatal care late [52]. Thus, some have suggested that immigrant status is not protective against abuse, but rather that abuse is under-reported by immigrant women [54] for reasons including male domination and patriarchy, lack of knowledge and access to social services, male attendance at social and health visits that discourage women from disclosing, financial dependency on their husbands, and fear of deportation if they report abuse [55].…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have reported lower rates of violence among pregnant immigrant women than we observed in this study [52,53], but found significant associations with poorer health behaviours, including not being current in vaccinations, not taking folic acid before pregnancy, and initiating prenatal care late [52]. Thus, some have suggested that immigrant status is not protective against abuse, but rather that abuse is under-reported by immigrant women [54] for reasons including male domination and patriarchy, lack of knowledge and access to social services, male attendance at social and health visits that discourage women from disclosing, financial dependency on their husbands, and fear of deportation if they report abuse [55].…”
Section: Discussionmentioning
confidence: 94%
“…However, while political conflict is probably a source of chronic stress for both groups, each population may still be affected differently by historical stressors. These may include the political status of Arabs, their trauma due to displacement (Daoud et al 2012) and systematic or institutional discrimination (Lewin et al 2006;Osman et al 2017), and rapid changes in lifestyle that have likely affected their health (Daoud et al 2009a), Jews, meanwhile, faced the horror or legacy of the Holocaust, repeated wars, and major cultural and social transitions following immigration, whether as refugees or otherwise (Shuval and Anson 2000). However, our findings suggest that the better SRH reported by Jewish participants might have been protected by their higher SES, higher social support, and lower chronic stress in recent decades (Soskolne and Manor 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The census data were reported at the level of dissemination areas (DAs), a census unit of 400 to 700 persons [ 38 ]. Only one woman in each DA was interviewed for the MES [ 5 , 39 ].…”
Section: Methodsmentioning
confidence: 99%